Effect of video-based health education intervention on insulin therapy among adults with diabetes mellitus in Dhulikhel Hospital: A randomized controlled trial - Manandhar, Subina; Shrestha, Satya; Shrestha, Bhawana; Nepal, Jyoti; Shrestha Karki, Sabina; Rangitkar, Sarishma; Devi Pun, Kunta (Journal of Chitwan Medical College, 2026)
Introduction: Proper insulin injection technique is essential for glycemic control and preventing complications in diabetes mellitus. This randomized controlled trial aimed to evaluate the effectiveness of a video-based educational intervention on insulin therapy knowledge and self-administration practices among adults with diabetes in Nepal.Methods: We conducted an open-label, two-arm RCT at Dhulikhel Hospital, Nepal, from Aug 2024 to Jul 2025. Eligible adults (≥18 years) with type 1 or type 2 diabetes on insulin therapy were randomized to an intervention group (video-based education plus usual care) or a control group (usual care only). Ethical approval was obtained, and the trial was registered. Outcomes were assessed using structured questionnaires and observational checklists. Analysis was performed in STATA 14.0 using descriptive statistics, chi-square tests, independent t-tests, and logistic regression to calculate adjusted odds ratios (aOR) with 95% confidence intervals (CI).Results: Of 126 participants enrolled, 94 completed follow-ups (intervention: n=41; control: n=53). The mean insulin injection practice score was significantly higher in the intervention group compared to controls (12.21 vs. 8.69, p